(untitled) (Journal of Hama University, 2026)
This study aimed to evaluate the toxic effect of methomyl on some blood biochemical parameters (alanine amino transferase (ALT), aspartate amino transferase (AST), alkaline phosphatase (ALP), creatinine) in rabbits ten days after oral administration. The experimental rabbits (average weight 800-1200 g), numbering (32) were divided into four groups (8 rabbits each), groups M2, M3، M4 received a daily oral dose of methomyl at concentrations of 1.5, 2.5 and 3.5 mg/kg, respectively, except for the control group M1 which was given only distilled water, Blood samples were collected from the ear vein before and after dosing for biochemical analysis, where the results showed a statistically significant increase (P≤0.05) in the levels of ALP, AST, ALT and creatinine enzymes for the treated groups M2, M3 and M4 compared to the control group M1. These results indicate that exposure to methomyl leads to significant changes in blood biochemical indicators, indicating a dysfunction in liver and kidney functions, and the severity of these changes is directly proportional to the increase in methomyl concentration.